Abundance and diversity of waterbirds around the Begnas Lake of Pokhara Valley, Nepal - Rajendra Basaula; Om Prakash Singh; Bhagawan Raj Dahal (Global Journal of Ecology - Peertechz Publications, 2023)
We studied the seasonal abundance and diversity of waterbirds around the Begnas lake of Pokhara Valley. The status of waterbirds in Begnas wetland is not documented so; we monitored the waterbirds using the point count method in 12 different plots around the lake and compared the seasonal abundance and diversity during the 2019 Summer and 2020 winter with 24 hours of observation in each plot. A total of 585 individuals of 25 waterbird species from 10 families were recorded during the study period. Among the recorded species two species were globally threatened and the remaining were the least concerned categories. The greater abundance of waterbirds was recorded during winter (t = -5.98, p < 0.001). The abundance of all feeding guilds was found higher during winter. Cattle egret was recorded with the greatest abundance (N = 85) and Relative abundance (RA = 14.52), it was followed by great cormorant (N = 57, RA = 9.74) and common pochard was the least abundant (N = 2, RA = 0.34). There was no seasonal variation in the Shannon Wiener index (H') and species evenness however, the species richness was higher during winter (W = 16.5, p < 0.01). Distance to the forest, road, and settlement did not affect the abundance and diversity of waterbirds however, the abundance of insectivore birds was increased with the decrease of distance to croplands (t = -3.13, p < 0.05). The Begnas wetland was found with a lower abundance and diversity of waterbirds in comparison to the Phewa and other wetlands of the Terai region of Nepal. The lake water pollution, infrastructural development, anthropogenic activities, recreational activities, and infestation of invasive plants like water hyacinth were the main threats to the waterbirds around Begnas lake. An awareness program about the conservation of waterbirds and regular monitoring of waterbirds in Begnas was recommended.